Hubungan Hipotensi Dengan Kejadian Post Operative Nausea And Vomiting (PONV) Pada Pasien Pasca Spinal Anestesi - Fransi Arsani; Cucu Raifatma Cipta; Heni Purwaningsih (Lembaga Pengembangan Kinerja Dosen, 2022)
Background : Spinal anesthesia is an anesthetic technique used to inhibit pain in some parts of the body. One of the complications that can occur is Post Operative Nausea and Vomiting (PONV). PONV can be caused by many factors, one of which is hypotension. Hypotension can lead to hypoxemia and hypoperfusion in the Chemoreceptor Trigger Zone (CTZ) as the center of vomiting stimulation. Objective : The study aimed to determine the relationship between hypotension and the incidence of Post Operative Nausea and Vomiting (PONV) in spinal anesthesia patients. Research Methods : This type of research is analytic observational with cross sectional research design. The population in this study were all patients undergoing spinal anesthesia at RSI Sultan Agung Semarang. Sampling in this study was to use the purposive sampling method of 53 samples and to use the chi square data analysis test. The research instrument used interviews and used observation sheets. Reseach Result : The most age of respondents in this study were 26-35 years old as many as 18 respondents (34.0%), the most gender was female 32 respondents (60.4%), and those who experienced hypotension were 29 respondents (54.7%) , while there were 30 respondents who experienced PONV (56,6%) .The results of the Chi-Square test to determine the relationship between hypotension and the incidence of Post Operative Nausea and Vomiting (PONV) yielded a result of 0.000 (P <0.5). The majority of respondents who experienced hypotension were 24 people (45.3). Conclusion : here is a significant relationship between hypotension and the incidence of Post Operative Nausea and Vomiting (PONV).